EFFECTS OF PRACTICAL CLASSES OF WATER LIFESAVING TRAINING COURSE ON TRANSFORMATION OF PARTICULAR ANTHROPOLOGICAL CHARACTERISTICS - Milan Cvetković; Goran Radivojević; Goran Dimitrić; Marko Jadranski; Damjan Jakšić; Dejan Orlić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The aim of this research was determination of effects of the practical classes of water lifesaving training course on course participants, in terms of particular anthropological characteristics. Suitable sample in experimental group were 22 participants on water lifesaving training course organized by Vojvodina Water Rescue Association, male and mean age 21 years, while the control group consisted of 23 students, also male and mean age 21 years, who worked at the regular syllabus for the subject Swimming in the third year of Faculty of Sport and Physical Education in Novi Sad. Changes that occurred in course participants and students of Faculty of Sport and Physical Education during a two-week practical training were monitored over the following tests and measures: 50 meters swim test, measuring the number of strokes to 50 meters swim test, 300 meters swim test, shuttle run test and body composition measurements. Research results obtained by MANCOVA indicate that significant changes were determined in transformation of evaluated anthropological characteristics, which confirms efficiency of the two-week practical classes of water lifesaving training course .